Long-term cardiopulmonary effects after Covid-19 infection. (14th October 2021) - Niebauer, J H; Binder- Rodriguez, C; Iscel, A; Klenk, S; Badr-Eslam, R; Cadjo, S; Kahr, M; Hoffman, S; Reiter-Malqvist, S; Boeck, R; Wenisch, C; Krestan, C; et al.
Abstract: Introduction: The severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) pandemic of 2020 has an influence on people's lives worldwide, impacting global health and putting pressure on health care systems. Multiple studies have described acute effects of the Covid-19 infection on the heart, but little is known about the long-term cardiac effects and complications after recovery. The aim of this analysis was to deliver a comprehensive report of symptoms and long-term impairment after Covid-19 infection. Methods: This study was a prospective, multicenter registry study. Patients with verified COVID-19 infection, who were treated at our dedicated COVID hospital (Klinik Favoriten), have been included in this study. In all patients, testing was performed approximately 6 months post discharge. During each study visit the following tests and investigations were performed: detailed patient history and clinical examination, transthoracic echocardiography, electrocardiography, cardiac magnetic resonance imaging (MRI), pulmonary computed tomography (CT) scan, lung function test, spiroergometry and six-minute walk test (6MWT), and a comprehensive list of laboratory parameters including cardiac bio markers such as brain natriuretic peptide (NTpro BNP) and troponin T. Results: In this interim analysis of an ongoing trial, the first 65 patients are presented. Baseline values are shown in table 1: 34 (59%) were male and the median age was 48.5 years (36.4–59.3). 86% of all patients included so far had an only mild to moderate course of disease and 14% of them had a severe course and were admitted to our intensive care unit. At the time of the study visit, the majority of patients still complained about symptoms: 40% presented with fatigue and weakness, 36% with exertional dyspnea, 21% with vertigo, 17% had an impaired taste or smell. Only 28% were completely asymptomatic (figure 1). From a cardiac perspective, the only abnormal findings noted in echocardiography studies were reduced left ventricular global longitudinal strain. Cardiac MRI revealed pericardial effusion in 19%, however, these were only minimal (≤9mm) and not visible in echocardiography. Furthermore, cardiac MRI showed positive late gadolinium enhancement in 11%. Pulmonary function tests were abnormal in 16%. Pulmonary CT scans showed post infectious residues like bilateral ground glass opacities and fibrosis in 45%. Exercise capacity as measured by the 6-minute walk test with BORG Dyspnea Score and by spiroergometry was reduced in almost 40% of our study participants. Conclusions: This interim analysis showed that most previously hospitalized patients still suffer from chronic fatigue, exertional dyspnea and impaired cardiopulmonary function after Covid-19 infection. Furthermore, even though cardiac and pulmonary imaging revealed numerous pathologic findings, and exercise capacity was reduced, no correlations could be found with persisting symptoms. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): Klink Favoriten and Medical University hospital Vienna